Nuclear DNA C‐values in 30 Species Double the Familial Representation in Pteridophytes - OBERMAYER, RENATE (Ann Bot, 2002)
Nuclear DNA C‐values and genome size are important biodiversity characters with fundamental biological significance. Yet C‐value data for pteridophytes, a diverse group of vascular plants with approx. 9000 extant species, remain scarce. A recent survey by Bennett and Leitch (2001, Annals of Botany 87: 335–345) found that C‐values were reported for only 48 pteridophyte species. To improve phylogenetic representation in this group and to check previously reported estimates, C‐values for 30 taxa in 17 families were measured using flow cytometry for all but one species. This technique proved generally applicable, but the ease with which C‐value data were generated varied greatly between materials. Comparing the new data with those previously published revealed several large discrepancies. After discounting doubtful data, C‐values for 62 pteridophyte species remained acceptable for analysis. The present work has increased the number of such species’ C‐values by 93 %, and more than doubled the number of families represented (from 10 to 21). Analysis shows that pteridophyte C‐values vary approx. 450‐fold, from 0·16 pg in Selaginella kraussiana to 72·7 pg in Psilotum nudum var. gasa. Superimposing C‐value data onto a robust phylogeny of pteridophytes suggests some possible trends in C‐value evolution and highlights areas for future work.